2007
DOI: 10.1152/jn.00355.2007
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Transmission at the Calyx of Held Under In Vivo–Like Activity Levels

Abstract: One of the hallmarks of auditory neurons in vivo is spontaneous activity that occurs even in the absence of any sensory stimuli. Sound-evoked bursts of discharges are thus embedded within this background of random firing. The calyx of Held synapse in the medial nucleus of the trapezoid body (MNTB) has been characterized in vitro as a fast relay that reliably fires at high stimulus frequencies (< or =800 Hz). However, inherently due to the preparation method, spontaneous activity is absent in studies using brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
172
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(196 citation statements)
references
References 51 publications
23
172
1
Order By: Relevance
“…Within the MNTB of adult rats, spontaneous discharge rates vary between zero and 133 Hz (mean 29 Hz, Tolnai et al, 2008). Similar values have been reported for gerbils (mean 25 Hz, Hermann et al, 2007). Even higher spontaneous rates were measured in adult mice (mean 71 Hz, range 0.4 -174 Hz, Lorteije et al, 2009).…”
Section: Physiological Implications Of CDI and Cdf At The Calyx Of Heldsupporting
confidence: 78%
“…Within the MNTB of adult rats, spontaneous discharge rates vary between zero and 133 Hz (mean 29 Hz, Tolnai et al, 2008). Similar values have been reported for gerbils (mean 25 Hz, Hermann et al, 2007). Even higher spontaneous rates were measured in adult mice (mean 71 Hz, range 0.4 -174 Hz, Lorteije et al, 2009).…”
Section: Physiological Implications Of CDI and Cdf At The Calyx Of Heldsupporting
confidence: 78%
“…We address tonic depression as a final candidate. Most cells are silent in slices, but in vivo their spontaneous activity may induce tonic short-term synaptic depression (Boudreau and Ferster, 2005;Reig et al, 2006;Hermann et al, 2007;Wang et al, 2010). In slices, a fast recovery phase has been observed, which depends on calcium buildup within the endbulb (Wang and Manis, 2008;Yang and Xu-Friedman, 2008).…”
Section: Low Release Probability Of the Endbulb Of Held In Vivomentioning
confidence: 99%
“…Recent work has shown that synaptic depression observed after long stimulation pauses in slice preparations might be less relevant in vivo (Hermann et al, 2007;Lorteije et al, 2009), mainly because of the high rates of spontaneous firing. Our work suggests that sudden increases in the rate of afferent fiber firing during sound-evoked activity might induce facilitation in the predepressed state of the synapse similar to the facilitation observed here in slice recordings.…”
Section: Possible Relevance Of Facilitation At a Depressing Synapsementioning
confidence: 99%
“…However, in vivo, neurons in the auditory brainstem fire spontaneously at a mean frequency of ϳ10 -30 Hz even in the absence of sound, and sound stimulation can transiently increase AP frequency to several hundred hertz (Sommer et al, 1993;Kopp-Scheinpflug et al, 2003;Hermann et al, 2007;Sonntag et al, 2009). In the present study, we used the most basic stimulation protocol designed to mimic the effect of spontaneous AP firing on short-term plasticity: a brief low-frequency train (10 or 20 Hz) to predepress synaptic transmission, followed immediately by a high-frequency train (see also Hermann et al, 2007). When applying this protocol to calyx of Held synapses in slices of young rats, we found that high-frequency trains (100 -200 Hz) caused robust facilitation of transmitter release relative to the predepressed level.…”
Section: Introductionmentioning
confidence: 99%